Academic Information System Governance Using The Framework It Balanced Scorecard And The Cobit Framework 2019 (Case Study: SMAN 15 Bandar Lampung) - Raden Arya Putra Martallata; Wasilah Wasilah (Prosiding International conference on Information Technology and Business (ICITB), 2022)
Today's information system is a very important thing and has become a basic need of an organization. The information system used can facilitate the organization's business processes in order to achieve goals. A good information system is able to provide effective and accurate information to all its users. SMA N 15 Bandar Lampung is one of the schools that implements the use of information technology into academic information systems. The management of the academic information system of SMA N 15 Bandar Lampung is not well managed, this is because in the application of IT there are several processes that are lacking and not in accordance with existing standards and rapid technological changes make the organization unable to adapt well, the academic information system is also slow in its activities unexpectedly resulting in unexpected system failures, lack of effectiveness of technical guidance related to the use of Siakad. With these conditions, an IT governance evaluation activity is needed which can later produce findings and recommendations that can be used by SMA N 15 Bandar Lampung. The method used is the selected IT Balanced Scorecard and COBIT 2019 framework. The results of the analysis of the distribution of questionnaires on the respondents got the average current value in the APO04, APO07, APO13, DSS02, DSS03 processes which was 3.47 which means that the assessment results on the academic information system of SMA N 15 Bandar Lampung have capability level 3 (established). All ongoing business processes have been implemented with planning and monitoring.Keywords—Information System Audit, COBIT 2019, IT Balanced Scorecard, IT Governance.